Investigation of Wear, Surface, Metallurgical and Mechanical Properties of Ti6Al4V Alloys Coated with PVD Method - Ada, Hakan; El Rubaye, Ahmed Qais Jabbar; Aşıkuzun, Elif; Mavi, Ahmet; Kaplan, Yavuz; Aksöz, Sinan (Politeknik Dergisi, 2025)
In this study, the PVD method coated cylindrical specimens produced from Ti6Al4V alloy with AlCrN, TiAlN, TiN, TiSiN coatings at different thicknesses. Profilometer tests were applied to determine the surface properties, such as coating thickness and surface roughness of the coated specimens, and microhardness and wear tests were applied to the specimens to determine the mechanical properties. In the profilometer measurements, the coating thicknesses were measured between 1-5 µm and the surface roughness values between 0.4 and 0.8 µm. From the microhardness and wear results, it was determined that thin-coated specimens gave better results than thick-coated specimens. While TiAlN had the best performance in microhardness and wear tests, this coating was followed by TiSiN, TiN and AlCrN coatings, respectively.